2020
DOI: 10.1002/jper.19-0606
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between alveolar bone morphology and volumetric dimensional changes in immediate maxillary implant placement: A 1‐year prospective cohort study

Abstract: Background After a single tooth extraction, remodelling processes are initiated and morphological changes occur in the alveolar bone. It has been suggested that implant placement in a fresh extraction socket may partly reduce the alveolar ridge contraction and that several factors like the thickness of the buccal bone wall and the size of the gap between the implant and the facial bone wall may play a role on peri‐implant tissues dimensional alterations. Methods Twenty‐six patients treated with single‐tooth ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Twenty‐one studies (Basler et al, 2018; Benic et al, 2017; Bittner et al, 2020; Canullo et al, 2018; Clementini et al, 2020; De Bruyckere et al, 2020; Eeckhout et al, 2020; Fischer et al, 2019; Friberg & Jemt, 2012; Hinze et al, 2018; Hosseini et al, 2020; Huber et al, 2018; Sanz Martin et al, 2016; Sanz‐Martin et al, 2019; Sapata et al, 2018; Schneider et al, 2011; Thoma et al, 2020; van Nimwegen et al, 2018; Wang et al, 2019; Wittneben et al, 2016; Zeltner et al, 2017) reported generating 3D digital models from constructed dental casts obtained with different impression materials (including silicone, alginate, polyether, and polyvinyl siloxane) with the use of desktop 3D optical scanners (indirect technique). The other eleven studies (Bertl et al, 2017; Borges et al, 2020; Cabanes‐Gumbau et al, 2019; Galarraga‐Vinueza et al, 2020; Jiang et al, 2020; Papi et al, 2020; Parvini et al, 2020; Rojo et al, 2018, 2020; Tian et al, 2019; Wei et al, 2019) had obtained the 3D digital models with the use of intra‐oral scanners (direct technique). Among them, six studies reported that a short‐span area was scanned (Galarraga‐Vinueza et al, 2020; Parvini et al, 2020; Rojo et al, 2018, 2020; Tian et al, 2019; Wei et al, 2019), while other articles did not provide information regarding the size of the scanned area.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Twenty‐one studies (Basler et al, 2018; Benic et al, 2017; Bittner et al, 2020; Canullo et al, 2018; Clementini et al, 2020; De Bruyckere et al, 2020; Eeckhout et al, 2020; Fischer et al, 2019; Friberg & Jemt, 2012; Hinze et al, 2018; Hosseini et al, 2020; Huber et al, 2018; Sanz Martin et al, 2016; Sanz‐Martin et al, 2019; Sapata et al, 2018; Schneider et al, 2011; Thoma et al, 2020; van Nimwegen et al, 2018; Wang et al, 2019; Wittneben et al, 2016; Zeltner et al, 2017) reported generating 3D digital models from constructed dental casts obtained with different impression materials (including silicone, alginate, polyether, and polyvinyl siloxane) with the use of desktop 3D optical scanners (indirect technique). The other eleven studies (Bertl et al, 2017; Borges et al, 2020; Cabanes‐Gumbau et al, 2019; Galarraga‐Vinueza et al, 2020; Jiang et al, 2020; Papi et al, 2020; Parvini et al, 2020; Rojo et al, 2018, 2020; Tian et al, 2019; Wei et al, 2019) had obtained the 3D digital models with the use of intra‐oral scanners (direct technique). Among them, six studies reported that a short‐span area was scanned (Galarraga‐Vinueza et al, 2020; Parvini et al, 2020; Rojo et al, 2018, 2020; Tian et al, 2019; Wei et al, 2019), while other articles did not provide information regarding the size of the scanned area.…”
Section: Resultsmentioning
confidence: 97%
“…In particular, in one study the calibration included performing all the measurements twice with an interval of 1 week (Sapata et al, 2018), while in another study the examiner had to repeat the measurements three times every other week on five randomly chosen participants (Wang et al, 2019). The coefficient of reproducibility was reported in six studies, ranging from 0.8 to 0.93 (Borges et al, 2020; Papi et al, 2020; Parvini et al, 2020; Sapata et al, 2018; van Nimwegen et al, 2018; Wang et al, 2019; Table 1). Additionally, in ten studies, the operator who had performed the volumetric analysis had been blinded to the interventions (Borges et al, 2020; Clementini et al, 2020; Fischer et al, 2019; Rojo et al, 2018, 2020; Sanz Martin et al, 2016; Sapata et al, 2018; Thoma et al, 2020; Wang et al, 2019; Zeltner et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations